Philippine libraries and librarianship an analysis of citations - David, Lourdes T. (1985)
The literature of the subject is its prime means of communication and reflects with great specificity the problem orientations of the researchers in that area of study and its growth points. This study used citation analysis to examine the literature of Philippine libraries and librarianship and to identify some of its characteristics. The sources of the citations gathered, organized and analyzed were 192 theses and special problems on library science and related subjects submitted to 24 Philippine schools from 1940 to 1980. Since the study is aimed at identifying characteristics of the literature of Philippine libraries and librarianship, only the citations to Filipiniana library science literature were analyzed using the techniques of citation analysis.